Optimal Determination Of Production Run And Initial Settings Of Process Parameters For A Deteriorating Process - Rahim, M.A. (2020)
This paper presents a generalized model for the optimal determination of a production run and the initial settings of the process mean and process variance for a deteriorating production process. It is assumed that the process deteriorates due to tool wear-out. The probability that the process deterioration starts at a random point in time follows an exponential distribution. Quality loss from the target values is measured using Taguchi's quadratic loss function. The time dependent maintenance cost and the salvage value of the equipment are included. The expressions for determining the optimal process mean and process variance are developed. Numerical examples are provided to demonstrate the application of the proposed model.